Bacterial load of conditioned pressure ulcers is not a predictor for early flap failure in spinal cord injury - Kamradt, Till; Klein, Sabrina; Zimmermann, Stefan; Schröder-Braunstein, Jutta; Hensel, Cornelia; Weidner, Norbert; Hug, Andreas (Spinal cord. Series and cases, 2017)
Objectives:Pressure ulcers impose a major lifetime medical problem to patients with high-grade spinal cord injury (SCI). For patients with stages 3-4 pressure ulcers, plastic surgery is often the only remaining treatment option. Despite considerable flap failure rates of around 30%, only sparse knowledge exists on predictors for flap failure. Hence, identification of predictors for flap failures is needed.Methods:We prospectively enrolled 38 SCI patients with stages 3-4 pressure ulcers scheduled for plastic surgery. Preoperative wound swabs, intraoperative tissue samples and postoperative drainage liquids were microbiologically analyzed. In multivariable logistic regression analyses, bacterial loads of deep tissue cultures of intraoperative samples as well as other clinical variables were analyzed with respect to the prediction of flap failures.Results:The flap failure rate was 27.5%. Bacterial loads of deep tissue cultures were not predictive for flap failure, neither was the colonization with a specific bacterial strain. We observed a considerable fluctuation of microbiological environment from initial swab cultures, intraoperative samples and postoperative drainage fluids. Antibioprophylaxis was sufficient in only 75% of deep tissue cultures and 69% of drainage fluids. Insufficient antibioprophylaxis was associated with a higher flap failure rates (odds ratio 6.3, confidence interval 1.2-41.0).Conclusion:After inpatient wound conditioning, bacterial load analysis of intraoperative wound tissue cultures is ineffective in order to predict flap failure rates in SCI patients with stages 3-4 pressure ulcers after flap surgery. Instead, insufficient antibioprophylaxis might be a factor contributing to flap failure.